Optimal mobile-phase composition for the resolution of deoxyribonucleosides in RP-HPLC - So, MS; Park, YK; Choi, DK; Row, KH (KOREAN SOC INDUSTRIAL ENGINEERING CHEMISTRY, 1998)
Five deoxyribonucleosides (dCyd, dUrd, dGuo, dThd, and dAdo) were separated by RP-HPLC under isocratic conditions. The volume percent of organic modifier was changed from 3.0 to 10.0 for methanol and acetonitrile, respectively. Potassium phosphate, sodium berate and TADP were used as buffer chemicals. The experimental results showed that for the separation of deoxyribonucleosides methanol was superior to acetonitrile as the organic modifier and the optimum condition of mobile phase was 5.0 vol. % of acetonitrile with 20 mM sodium berate.
Keywords: PERFORMANCE LIQUID-CHROMATOGRAPHY; SOLVOPHOBIC DRIVING FORCES; UV-ABSORBING COMPOUNDS; NUCLEOSIDES; IDENTIFICATION; QUANTITATION; REVISIONIST; SEPARATION; NONPOLAR; BASES